2010
DOI: 10.1029/2010jd014398
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterodyne Imager for Mesospheric Radicals on STPSat‐1

Abstract: [1] The Spatial Heterodyne Imager for Mesospheric Radicals (SHIMMER) was a high-resolution, near ultraviolet spectrometer that imaged the Earth's limb for 2.5 years between March 2007 and October 2009. The instrument used the Spatial Heterodyne Spectroscopy technique for the first time on a satellite and successfully demonstrated its capabilities. SHIMMER measured the solar resonance fluorescence of the OH A 2 S + -X 2 P (0, 0) band around 309 nm, which allows the retrieval of mesospheric OH density profiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 39 publications
2
48
2
Order By: Relevance
“…Taken together, the net effect of these changes is to reduce the calculated OH by about 6% as compared with our calculations in Englert et al . []. While this difference is small, since the calculated OH was already about 10% lower than the observations in the Englert et al .…”
Section: Approach To Model‐measurement Comparisonsmentioning
confidence: 57%
See 1 more Smart Citation
“…Taken together, the net effect of these changes is to reduce the calculated OH by about 6% as compared with our calculations in Englert et al . []. While this difference is small, since the calculated OH was already about 10% lower than the observations in the Englert et al .…”
Section: Approach To Model‐measurement Comparisonsmentioning
confidence: 57%
“…Thus, first results from the Spatial Heterodyne Imager for Mesospheric Radicals (SHIMMER) [ Englert et al ., ] and the Aura Microwave Limb Sounder (MLS) [ Pickett et al ., ] found good agreement between their data and models. Englert et al [] presented arguments that the MAHRSI data may have had an unidentified calibration problem which led to the somewhat lower values of hydroxyl abundance first reported by Summers et al . [] and concluded that there is no model overprediction of mesospheric odd hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Section 2 presents 3 NH seasons of mesospheric cloud data from two instruments, the Solar Occultation for Ice Experiment (SOFIE) and the Spatial Heterodyne Spectrometer for Mesospheric Radicals (SHIMMER). SOFIE is on board the NASA Aeronomy of Ice in the Mesosphere (AIM) satellite (Russell et al, 2009) (Englert et al, 2010). Both SHIMMER and SOFIE observed mesospheric clouds during the 2007, 2008 and 2009 Northern summer seasons, but, as we will discuss, using quite different observational techniques and from different orbits.…”
Section: Introductionmentioning
confidence: 99%
“…More details on a technique that can be used to correct for the thermal defocus effect in an SHS instrument can be found in Ref. 15. It is worth noting that especially for high fringe frequencies, defocusing will result in a fringe contrast reduction and therefore a decrease in the signal-to-noise ratio, which cannot be recovered.…”
Section: Thermal Considerationsmentioning
confidence: 99%
“…15 Both of these effects can be corrected in the data analysis if the temperature is stable during an individual exposure since (1) the spectral shape of the measured signal is known (except for the magnitude of the absorption) which allows the determination of the wavelength scale for each measured spectrum from the spectrum itself and (2) the absorption measurement is self-calibrating since the baseline is measured with each exposure. More details on a technique that can be used to correct for the thermal defocus effect in an SHS instrument can be found in Ref.…”
Section: Thermal Considerationsmentioning
confidence: 99%